SUPERVISI PELAKSANAAN LAPIS AC - BC PADA KEGIATAN PENINGKATAN RUAS JALAN MULYA SARI - PURWOSARI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN KOTA PALEMBANG - Senzini, Yang (Ensiklopedia of Journal, 2024)
Highways are land lanes above the earth's surface that are made by humans with shapes, sizes and types of construction so that they can be used to channel the traffic of people, animals and vehicles that transport goods from one place to another easily and quickly. Clarkson H. Oglesby, 1999). For a good highway planning, the geometric shape must be determined in such a way that the road concerned can provide optimal services to traffic according to its function, because the ultimate goal of this geometric planning is to produce a safe infrastructure, efficient traffic flow and maximize traffic flow. the ratio of the level of use of costs also provides a sense of security and comfort to road users. This research is a research study in the field which aims to find out whether the method of implementing the AC – BC (Asphalt Concrete – Binder Course) work on the Mulyasari-Purwosari axle road improvement project, Kec. Tanjung Lago, Kab. Banyuasin is in accordance with the general specifications of the 2018 Binamarga. Based on the results of the study, the stages of the AC-BC surface layer work on the Mulyasari-Purwosari axle road improvement project, Kec. Tanjung Lago, Kab. Banyuasin includes road cleaning, prime coat watering, material transportation, laying, compaction, and field testing of core drills. So the method of implementing the AC-BC surface layer work on the Mulyasari-Purwosari axle road improvement project, Kec. Tanjung Lago, Kab. Banyuasin does not meet the 2018 Highways Specification standard.Keywords: Method of Implementation of AC-BC Pavement Layer on raising of the Mulya Sari – Purwosari axle road, Kec. Tanjung Lago, Kab. Banyuasin